Light–valley interactions in 2D semiconductors - Mak, Kin Fai; Xiao, Di; Shan, Jie (Nature photonics, 2018)
The emergence of two-dimensional Dirac materials, particularly transition metal dichalcogenides (TMDs), has reinvigorated interest in valleytronics, which utilizes the electronic valley degree of freedom for information storage and processing. Here, we review the basic valley-dependent properties and their experimental demonstrations in single-layer semiconductor TMDs with an emphasis on the effects of band topology and light–valley interactions. We also provide a brief summary of the recent advances on controlling the valley degree of freedom in TMDs with light and other means for potential applications. Valleytronics in single-layer semiconductors is reviewed with an emphasis on controlling the valley degree of freedom with light as well as potential applications.